Production, characterization, and biocompatibility of polycaprolactone/polylactic acid coaxial nanofiber patches based on bacterial cellulose from orange peels - Sayan, Melike Naz; Avci, Aysenur; Sulutas, Rabia Betul; Calhan, Aslihan; Cesur, Sumeyye; Sahin, Ali; Gunduz, Oguzhan; Ustundag, Cem Bulent (SPRINGERNATURE, 2025)
Polycaprolactone (PCL) /polylactic acid (PLA) coaxial electrospun nanofiber patches were produced with bacterial cellulose (BC) obtained by recycling orange peels, and their effect on human dermal fibroblast cell line was investigated. Biodegradable nanofibers composed of PLA and PCL are frequently used in biomedical applications due to their favorable mechanical and biocompatible properties. However, the incorporation of bioactive molecules such as ascorbic acid and the integration with a non-synthetic polymer such as bacterial cellulose can enable a new and different focus on the interaction with PCL/PLA. The produced coaxial nanofiber patches were compared based on two different BC concentrations and the presence or absence of ascorbic acid. In the coaxial structure, the core layer consisted of PCL/PLA, while the shell layer was composed of BC. Scanning electron microscopy (SEM) analysis revealed that the thickest fibers were observed in the pure PCL/PLA nanofiber patches, whereas the addition of ascorbic acid led to a noticeable reduction in fiber thickness. Furthermore, increasing the BC ratio resulted in a higher incidence of fiber breakage. According to the swelling and degradation test results, BC increased the swelling capacity of the material, while PCL/PLA slowed down the biodegradation rate. The coaxial nanofiber structure, with BC as the shell and PCL/PLA as the core, exhibited biocompatibility by supporting dermal cell viability, proliferation, and adhesion over 1, 4, and 7 days of observation.
Keywords: Orange peel; BC; Electrospinning; Fibroblast cell; Ascorbic acid; Biomaterials; PCL; PLA; ELECTROSPUN NANOFIBERS; IN-VITRO; DEGRADATION; CHITOSAN; Materials Science